PENGARUH DIVIDEN PER SHARE (DPS), DIVIDEN PAYOUT RATIO (DPR), PRICE TO BOOK VALUE (PBV), DEBT TO EQUITY RATIO (DER), NET PROFIT MARGIN (NPM) DAN RETURN ON ASSET (ROA)TERHADAP HARGA SAHAM PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR MAKANAN DAN MINUMAN DALAM KEMASAN YANG TERDAFTAR DI BEI - Edhi Asmirantho; Elif Yuliawati (Universitas Pakuan, 2015)
This research was conducted in order to test the influence of DPS, DER, PBV, DER, NPM and ROA on stock prices in the manufacturing sub-sectors of food and beverages in containers that are listed in the Indonesia Stock Exchange. The research technique that used was purposive sampling with criteria: (1) The Company actively listed on the Indonesia Stock Exchange for seven consecutive years. (2) The Company periodically publish financial statements of the period from 2007 to 2013. (3) Each company has a complete data needed in the research. (4) The CompanThis research was conducted in order to test the influence of DPS, DER, PBV, DER, NPM and ROA on stock prices in the manufacturing sub-sectors of food and beverages in containers that are listed in the Indonesia Stock Exchange. The research technique that used was purposive sampling with criteria: (1) The Company actively listed on the Indonesia Stock Exchange for seven consecutive years. (2) The Company periodically publish financial statements of the period from 2007 to 2013. (3) Each company has a complete data needed in the research. (4) The Company regularly distribute dividends for seven period. The analysis technique that used was multiple linear regression and hypothesis testing using t-statistic to test the partial regression coefficient and F-statistic to test the effect simultaneously with a confidence level of 5%. Besides all the variables have been tested with the classical assumption. The results of this research showed that all variables passed the test classic assumptions and fit for use as research data. Statistical t test results showed that the variables PBV, NPM and ROA were partial positive and significant impact on stock prices, other variables in this research that the Parliament has negative and insignificant. DPS and DER have no effect and significant to price stock. The results of F test showed that all variables in this study positive and significant effect on the price stock. The results of regression estimation shows the predictive capability of all independent variables on stock prices by 91.1%. While the rest of 8.9% influenced by other factors beyond this research. These results can be used to guide the investors before investing the stock market.Keywords: Dividend Per Share (DPS), Dividend Payout Ratio (DPR), Price to Book Value (PBV), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Return on Assets (ROA).y regularly distribute dividends for seven period. The analysis technique that used was multiple linear regression and hypothesis testing using t-statistic to test the partial regression coefficient and F-statistic to test the effect simultaneously with a confidence level of 5%. Besides all the variables have been tested with the classical assumption. The results of this research showed that all variables passed the test classic assumptions and fit for use as research data. Statistical t test results showed that the variables PBV, NPM and ROA were partial positive and significant impact on stock prices, other variables in this research that the Parliament has negative and insignificant. DPS and DER have no effect and significant to price stock. The results of F test showed that all variables in this study positive and significant effect on the price stock. The results of regression estimation shows the predictive capability of all independent variables on stock prices by 91.1%. While the rest of 8.9% influenced by other factors beyond this research. These results can be used to guide the investors before investing the stock market.Keywords: Dividend Per Share (DPS), Dividend Payout Ratio (DPR), Price to Book Value (PBV), Debt to Equity Ratio (DER), Net Profit Margin (NPM), and Return on Assets (ROA).